Biocontrol of aflatoxins using non-aflatoxigenic Aspergillus flavus: a literature review. - Khan, Rahim; Mohamad Ghazali, Farinazleen; Mahyudin, Nor Ainy; Putra Samsudin, Nik Iskandar (Multidisciplinary Digital Publishing Institute, 2021)
Aflatoxins (AFs) are mycotoxins, predominantly produced by Aspergillus flavus, A. parasiticus, A. nomius, and A. pseudotamarii. AFs are carcinogenic compounds causing liver cancer in humans and animals. Physical and biological factors significantly affect AF production during the pre-and post-harvest time. Several methodologies have been developed to control AF contamination, yet; they are usually expensive and unfriendly to the environment. Consequently, interest in using biocontrol agents has increased, as they are convenient, advanced, and friendly to the environment. Using non-aflatoxigenic strains of A. flavus (AF−) as biocontrol agents is the most promising method to control AFs’ contamination in cereal crops. AF− strains cannot produce AFs due to the absence of polyketide synthase genes or genetic mutation. AF− strains competitively exclude the AF+ strains in the field, giving an extra advantage to the stored grains. Several microbiological, molecular, and field-based approaches have been used to select a suitable biocontrol agent. The effectiveness of biocontrol agents in controlling AF contamination could reach up to 99.3%. Optimal inoculum rate and a perfect time of application are critical factors influencing the efficacy of biocontrol agents.